ANALISIS TENTANG INTERAKSI SOSIAL SISWA KELAS X SMA SANTUN UNTAN PONTIANAK - Cindy Aprilianensi; Indri Astuti; Luhur Wicaksono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This research analysis containing abaud Social Interaction of Class X Students of Senior Hight School Santun Untan Pontianak. The problem in this study is how is the ability to communicate, the ability to behave, the ability to behave in groups, the ability to social contact in achieving social interaction in class X Senior Hight School Santun Untan Pontianak. This study aims to obtain information and describe communication skills, attitude skills, group behavior skills, and social contact skills. The method in this research is descriptive method with the form of research used is survey. The subjects in this study were 19 class X IPA students. Techniques and tools used in this research are indirect communication techniques using a questionnaire. Based on the results of the analysis of social interaction, it can be seen in the acquisition of the percentage of each aspect, including: 1) The ability to communicate was 84.79% 2) The ability to behave was 79.82%, 3) The ability to behave in the group 76.84%, 4 ) the ability to social contact obtained results 76.80%. Based on the description above, in general the analysis of social interaction has been successfully carried out on class X SMA Santun Untan Pontianak. Keywords : Analysis of Interaction Social,Comunication, Attitude